The Role of Endogenous IFN-β in the Regulation of Th17 Responses in Patients with Relapsing-Remitting Multiple Sclerosis - Tao, Yazhong; Zhang, Xin; Chopra, Manisha; Kim, Ming-Jeong; Buch, Kinnari R; Kong, Dehan; Jin, Jianping; Tang, Yunan; Zhu, Hongtu; Jewells, Valerie; Markovic-Plese, Silva (The Journal of immunology (1950), 2014)
IFN-β has been used as a first-line therapy for relapsing-remitting multiple sclerosis (RRMS). Because only a few studies have addressed the role of endogenous IFN-β in the pathogenesis of the disease, our objective was to characterize its role in the transcriptional regulation of pathogenic Th17 cytokines in patients with RRMS. In vitro studies have demonstrated that IFN-β inhibits IL-17A, IL-17F, IL-21, IL-22, and IFN-γ secretion in CD4+ lymphocytes through the induction of suppressor of cytokine secretion 1 and suppressor of cytokine secretion 3. We found that patients with RRMS have increased serum and cerebrospinal fluid Th17 (IL-17A and IL-17F) cytokine levels in comparison with the control subjects, suggesting that deficient endogenous IFN-β secretion or signaling can contribute to the dysregulation of those pathogenic cytokines in CD4+ cells. We identified that the endogenous IFN-β from serum of RRMS patients induced a significantly lower IFN-inducible gene expression in comparison with healthy controls. In addition, in vitro studies have revealed deficient endogenous and exogenous IFN-β signaling in the CD4+ cells derived from patients with MS. Interestingly, upon inhibition of the endogenous IFN-β signaling by silencing IFN regulatory factor (IRF) 7 gene expression, the resting CD4+ T cells secreted significantly higher level of IL-17A, IL-17F, IL-21, IL-22, and IL-9, suggesting that endogenous IFN-β suppresses the secretion of these pathogenic cytokines. In vivo recombinant IFN-β–1a treatment induced IFNAR1 and its downstream signaling molecules’ gene expression, suggesting that treatment reconstitutes a deficient endogenous IFN-β regulation of the CD4+ T cells’ pathogenic cytokine production in patients with MS.